EXCELLENT ACADEMIC ACHIEVEMENT: DO INTELLECTUAL HUMILITY AND EMOTIONAL INTELLIGENCE MATTER? - Aurelius Ratu; Ni Gusti Made Rai; Eka Dian Savitri (LPMPP Universitas Negeri Yogyakarta, 2021)
Since emotional intelligence receives much attention in the context of academic success and intellectual humility is frequently studied in the context of career path, research concerning the relationship between emotional intelligence and intellectual humility on academic achievement is a necessity. This study aims to investigate that relationship while contributing to higher education on the insight to an employable graduate. The quantitative approach was implemented as the research framework by applying independent t-test and multiple regression in the first and second phases respectively. We found that the total score of intellectual humility and emotional intelligence for students (male and female) in the first year have a significant effect, while only the total score of intellectual humility among male in the second year has a significant effect on GPA (n = 531). Acknowledging academic achievement is an important variable in student’s academic process and intellectual humility to continuously plan, adapt, adjust, and evaluate their set of competencies, while simultaneously their engagement in a non-academic activity should be fostered. Besides, we suggest a mentor programme on both career and academic dimensions to make them enjoy and comfortable during their educational process. An understanding of IH during the educational process is impossible without serious attention to emotion, including the religious dimension.